CONVERGENCE RATE OF THE PHAM DINH-L E THI'S ALGORITHM FOR THE TRUST-REGION SUBPROBLEM - Hoàng Ngọc Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
We obtain sufficient conditions for the linear convergence of the iterative sequences produced by the Pham Dinh-Le Thi Algorithm for the trust-region sub-problem. In addition, we give two examples to show that, if the sufficient conditions are not satisfied, then the DCA sequences may not be linearly convergent.